2018
DOI: 10.3389/fmicb.2018.02767
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Isolated From Retail Meat and Meat Products in China: Incidence, Antibiotic Resistance and Genetic Diversity

Abstract: This study was to estimate the prevalence and characteristics of Staphylococcus aureus from 1,850 retail meat and meat products in China during July 2011 to June 2016. The samples were collected covering most provincial capitals in China, including 604 raw meat, 601 quick-frozen meat, and 645 ready-to-eat meat. Using the qualitative and quantitative methods, all 39 cities had S. aureus-positive samples, and S. aureus was detected in 35.0% (647/1,850) of the samples. The levels of S. aureus in retail meat showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
118
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(152 citation statements)
references
References 86 publications
19
118
15
Order By: Relevance
“…However, the prevalence obtained in this study was higher than that previously observed by Mairi et al (2019), with rate of 8Á6%. A higher prevalence of S. aureus have been observed in other countries concerning various foodstuffs, including raw milk and dairy products (Rola et al 2015;Mehli et al 2017;Obaidat et al 2018;Ahmed Abdel-Hameid et al 2019;Papadopoulous et al2019b), meat and meat products (Tang et al 2017;Wu et al 2018) and ready to eat products (Islam et al 2019). The differences between results obtained from various studies about prevalence rates of S. aureus may be related to different attributes, including sources of samples, geographical origin, inappropriate antimicrobial administrations, sensitivity of the identification methods, sample size, storage and handling of samples (Al-Ashmawy et al 2016;Gharsa et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…However, the prevalence obtained in this study was higher than that previously observed by Mairi et al (2019), with rate of 8Á6%. A higher prevalence of S. aureus have been observed in other countries concerning various foodstuffs, including raw milk and dairy products (Rola et al 2015;Mehli et al 2017;Obaidat et al 2018;Ahmed Abdel-Hameid et al 2019;Papadopoulous et al2019b), meat and meat products (Tang et al 2017;Wu et al 2018) and ready to eat products (Islam et al 2019). The differences between results obtained from various studies about prevalence rates of S. aureus may be related to different attributes, including sources of samples, geographical origin, inappropriate antimicrobial administrations, sensitivity of the identification methods, sample size, storage and handling of samples (Al-Ashmawy et al 2016;Gharsa et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Based on the MLST results, 412 S. aureus isolates were divided into 76 STs, with fewer MRSA isolates (14 STs) than MSSA isolates (69 STs), indicating that MRSA isolates were more genetically stable than MSSA isolates. The most commonly reported S. aureus isolates in China are diverse and include ST1 (36), ST6 (20), ST5 (37), and ST188 (38) according to different regions, ages, and resources. Similarly, many different MSSA isolates have been identified throughout China, including ST7 and ST188 (39).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological typing methods, such as MLST, are considered crucial for studying the prevalence of foodborne bacteria. MLST is a nucleotide sequence-based approach for the unambiguous characterization of isolates that has been broadly used for epidemiological typing and risk analyses of many pathogenic bacteria, such as S. aureus (Wu et al, 2018), L. monocytogenes (Wu et al, 2016), Cronobacter spp. (Xu et al, 2015), Salmonella (Matheson et al, 2010), and B. cereus (Cardazzo et al, 2008;Yang et al, 2017;Zhang et al, 2017;Yu et al, 2019).…”
Section: Genetic Diversity Of B Cereus In Rte Foodsmentioning
confidence: 99%